A Handbook for Tax Simplification - International Finance Corporation (World Bank, Washington, DC, 2017)
The purpose of this handbook is to provide policy makers with a framework to assess a tax system in its entirety, measure its various parameters and how it is administered, and defines best practices for tax policy and administration that will yield a tax system that is simple and predictable and does not create an undue burden on private enterprise. This handbook is primarily designed for policy makers and tax practitioners. The goal is to analyze the impact of income tax, the value added tax (VAT), and other local taxes that are imposed on business. This handbook does not analyze the effects of trade and labor taxes such as social security. The administration of the customs duty is unique and has been addressed extensively in the literature on customs modernization. Labor taxes primarily imposed on salaried individuals are not covered by this handbook, even though their incidence affects business. VAT has been included even though it is a tax on consumption because the administrative burden to comply with it is primarily on business.